Constructing Eight Smart Building–Safety Dimensions Through PRISMA Mapping and Fuzzy Mamdani Evaluation - Adwitya Bhaskara; Fitri Nugraheni; Sri Kusumadewi (G-Tech: Jurnal Teknologi Terapan, 2026)
The integration of smart buildings and Internet of Things (IoT)–based safety systems is becoming increasingly important in response to the growing demand for intelligent, safe, and responsive buildings. However, prior studies predominantly focus on technological performance or isolated safety applications, with limited attention to structured readiness mapping at the dimensional level. Addressing this gap, this study proposes a novel eight-dimensional smart building–safety readiness model by integrating a PRISMA 2020–guided systematic literature review (SLR), concept mapping, and Fuzzy Mamdani evaluation. The SLR resulted in five key articles that underpin eight core dimensions: Building Management, Automation and Control, IoT Connectivity, Decision Analytics, Adaptive Response, Safety and Maintenance, Energy and Sustainability, and Automation Dominance. The Fuzzy Mamdani analysis was applied to 23 validated readiness indicators and showed that all dimensions fall within the Average category, with fuzzy values ranging from 54 to 61. These findings indicate that the readiness level for implementing smart building–safety in Indonesia is at a stable intermediate stage, with no dimension lagging significantly behind. Practically, the proposed dimensional model can support policymakers in prioritizing regulatory focus, assist building practitioners in identifying readiness gaps, and provide researchers with a structured framework for advancing smart building–safety integration.